A rapid prototyping flame-retardant nylon composite material and its preparation method and application

By combining MXD6 resin, decabromodiphenylethane flame retardant and polyethylene glycol with a specific number average molecular weight, the problem that existing flame retardant nylon composite materials cannot be rapidly formed is solved, and the effect of rapid molding is achieved while ensuring the V-0 flame retardant grade.

CN117487347BActive Publication Date: 2025-03-25JIANGSU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311296048.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-03-25
Estimated Expiration
2043-10-09

AI Technical Summary

Technical Problem

While ensuring excellent flame retardant performance, existing flame retardant nylon composite materials cannot have the ability to quickly form, and it is difficult to meet the dual requirements of electronic and electrical components for rapid form and flame retardant performance.

Method used

By selecting a specific type of nylon resin (MXD6 resin) combined with decabromodiphenyl ethane flame retardant and a specific number average molecular weight polyethylene glycol, the rapid molding ability of the nylon composite is significantly improved by utilizing the high glass transition temperature of the MXD6 resin and the low specific heat capacity of the decabromodiphenyl ethane flame retardant.

Benefits of technology

It has achieved the excellent rapid molding ability of nylon composites to maintain good flame retardant performance (to achieve V-0 grade) and to maintain the excellent rapid molding ability, which can keep the deformation of injection molded parts small and quickly cool and set in a short forming cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004482952450000061
    Figure BDA0004482952450000061
  • Figure BDA0004482952450000062
    Figure BDA0004482952450000062
  • Figure BDA0004482952450000063
    Figure BDA0004482952450000063
Patent Text Reader

Abstract

The present invention discloses a rapid prototyping flame-retardant nylon composite material, and a preparation method and application thereof. The rapid prototyping flame-retardant nylon composite material of the present invention comprises the following components by weight: 70 to 90 parts of MXD6 resin; 18 to 24 parts of decabromodiphenylethane; 1 to 5 parts of polyethylene glycol; wherein the number average molecular weight of the polyethylene glycol is 1000 to 6200. The rapid prototyping flame-retardant nylon composite material of the present invention significantly improves its rapid prototyping ability while maintaining the good flame retardancy of the nylon composite material by selecting a specific type of nylon resin, combining it with a decabromodiphenylethane flame retardant and polyethylene glycol of a specific number average molecular weight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer compound compositions, and more specifically to a rapid prototyping flame-retardant nylon composite material and a preparation method and application thereof. Background Art

[0002] Polyamide resin has excellent mechanical properties, barrier properties, heat resistance, wear resistance, chemical corrosion resistance and other comprehensive properties. Its composite materials are widely used in machinery manufacturing, household appliances, power tools, electronic appliances, transportation and other fields, especially in electronic and electrical products, such as connectors, relays, capacitors and other electronic and electrical components must meet UL94V0 and glow wire ignition temperature GWIT775℃ requirements. Therefore, flame retardants are usually added to improve their flame retardant properties. Compared with other flame retardants, environmentally friendly brominated flame retardants have the advantages of low precipitation, high efficiency flame retardancy and color matching, and are widely used in electronic and electrical component products.

[0003] Moreover, existing electronic and electrical components are usually molded by injection molding, with one mold molding dozens to dozens of products. The molding cycle is very short, generally required to be within 10 seconds. This requires that polyamide composite materials not only need to have excellent low warpage performance and keep the deformation of injection molded parts small within a short molding cycle; they also need to have rapid cooling capabilities and can be quickly cooled and molded within a short molding cycle, and are not prone to large post-shrinkage and post-deformation.

[0004] In order to solve the above problems, various nucleating agents are often added to shorten the injection molding cycle of polyamide composite materials. For example, the prior art discloses a rapid prototyping nylon 66 resin and a preparation method thereof. A nucleating agent is added during the nylon polymerization process to accelerate the crystallization process of the nylon molecular chain, increase its crystallization temperature and crystallization rate, and thus achieve nylon 66 rapid prototyping. However, the material does not contain flame retardant components, and different flame retardant components will affect the crystallization properties of nylon, thereby affecting the rapid prototyping ability of nylon composite materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects and shortcomings of existing flame-retardant nylon composite materials that they cannot have rapid prototyping capabilities while ensuring excellent flame-retardant properties, and to provide a rapid prototyping flame-retardant nylon composite material. By selecting a specific type of nylon resin, combining it with a decabromodiphenylethane flame retardant and a polyethylene glycol with a specific number average molecular weight, the rapid prototyping capability of the nylon composite material is significantly improved while maintaining good flame retardancy.

[0006] Another object of the present invention is to provide a method for preparing a rapid prototyping flame retardant nylon composite material.

[0007] Another object of the present invention is to provide the use of the rapid prototyping flame-retardant nylon composite material in the preparation of electronic and electrical component materials.

[0008] Another object of the present invention is to provide an electronic and electrical component made of the rapid prototyping flame-retardant nylon composite material.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0010] The present invention protects a rapid prototyping flame-retardant nylon composite material, which comprises the following components by weight:

[0011] MXD6 resin 70-90 parts;

[0012] 18-24 parts of decabromodiphenylethane;

[0013] 1-5 parts of polyethylene glycol;

[0014] Wherein, the number average molecular weight of the polyethylene glycol is 1000-6200.

[0015] The number average molecular weight of the above polyethylene glycol can be obtained by gel permeation chromatography-multi-angle laser scattering (SEC-MALLS) testing. The specific operation is: weigh a certain amount of polyethylene glycol (accurate to 0.01 mg) and tetrahydrofuran (accurate to 0.1 mL) to prepare a dilute polyethylene glycol solution. After standing for 24 hours, the sample solution is filtered through a semipermeable membrane with a pore size of 0.45 μm and then injected into the SEC-MALLS test system for measurement to obtain the corresponding data.

[0016] The present invention selects a specific type of nylon resin, combines it with a decabromodiphenylethane flame retardant and a polyethylene glycol with a specific number average molecular weight, and significantly improves the rapid prototyping ability of the nylon composite material while maintaining good flame retardancy. The inventor has found through a large number of studies that the combination of MXD6 resin, decabromodiphenylethane flame retardant and a polyethylene glycol with a number average molecular weight of 1000 to 6200 can make the nylon composite material still have good strength at a higher temperature through the high glass transition temperature of the MXD6 resin, because the segment movement of the polymer material is limited below the glass transition temperature, reflecting the solid-state characteristics, which provides a basis for high-beat rapid prototyping; compared with other flame retardants, decabromodiphenylethane flame retardant has a lower specific heat capacity, can release heat to other media (such as air, metal molds filled with cooling water, etc.) more quickly, which is conducive to reducing the temperature of the injection molded product when it is ejected from the mold. At the same time, polyethylene glycol with a specific number average molecular weight can quickly migrate to the surface of the polymer to form a melt film to assist in the demolding of flame-retardant nylon composite materials; more importantly, the decomposition products of polyethylene glycol have good volatility, and unlike most conventional lubricants, they accumulate over a long period of time during the use of the mold to form muddy precipitates, thereby clogging the exhaust grooves of the mold and affecting the molding of the product.

[0017] In the above-mentioned nylon composite material system, the number average molecular weight of polyethylene glycol plays a key role. When the number average molecular weight of polyethylene glycol is too low, its thermal stability is relatively poor, and it is easy to decompose under the action of heat such as extrusion molding and injection molding, and cannot play the role of lubrication and demolding; when the number average molecular weight of polyethylene glycol is too high, it is excessively entangled with the MXD6 resin molecular chain, resulting in a slower rate of polyethylene glycol migration to the polymer surface, and also no obvious improvement on demolding, which leads to a longer cooling time of the part, making the rapid molding ability of the flame-retardant nylon composite material worse.

[0018] In addition, experiments have shown that, in the present invention, when the amount of polyethylene glycol added is 1 to 5 parts, the overall effect is better; when the amount of polyethylene glycol added is too little, the demoulding improvement effect on the composite material is not obvious, and a long cooling time is still required for smooth demolding; when the amount of polyethylene glycol added is too much, it has a certain negative impact on the flame retardant properties of the composite material, and the composite material can only achieve V-2 flame retardancy.

[0019] It should also be noted that the present invention has no special requirements for the melting point and viscosity of the MXD6 resin. The MXD6 resin with a conventional melting point and viscosity can achieve the purpose of the present invention. Specifically, the melting point range of the above-mentioned MXD6 resin is generally 237°C to 238°C, and the relative viscosity is generally 2.0 to 3.0. Moreover, the MXD6 resin is a matrix resin, and its mass percentage relative to the rapid prototyping flame-retardant nylon composite material is ≥67%.

[0020] Preferably, the rapid prototyping flame-retardant nylon composite material comprises the following components in parts by weight:

[0021] MXD6 resin 75-85 parts;

[0022] 20-22 parts of decabromodiphenylethane;

[0023] 1 to 3 parts of polyethylene glycol.

[0024] Optionally, the number average molecular weight of the polyethylene glycol is 1000-1500, 1500-2000, 2000-2500, 2500-3000, 3000-3500, 3500-4000, 4000-4500, 4500-5000, 5000-5500, 5500-6200; specifically, it may be 1000, 1500, 2000, 3000, 4000 or 6200.

[0025] Specifically, the rapid prototyping flame-retardant nylon composite material further comprises 6 to 10 parts by weight of antimony trioxide. Preferably, the rapid prototyping flame-retardant nylon composite material further comprises 7 to 9 parts by weight of antimony trioxide.

[0026] Antimony trioxide acts as a flame retardant synergist. When combined with decabromodiphenylethane flame retardant, it will produce antimony bromide and antimony oxybromide, which have better flame retardant effect.

[0027] Specifically, the mass percentage of the polyethylene glycol relative to the rapid prototyping flame-retardant nylon composite material is 0.84% ​​to 4.85%.

[0028] In a specific embodiment, the relative viscosity of the MXD6 resin of the present invention is 2.0 to 3.0 as measured according to ISO 307-2007 standard. The present invention has no special requirements for the viscosity of the MXD6 resin, and the MXD6 resin of conventional viscosity can achieve the purpose of the present invention. When the relative viscosity of the MXD6 resin is 2.0 to 3.0, the rigidity and toughness of the composite material can be further balanced, and the overall effect is better.

[0029] The present invention also protects a method for preparing the above-mentioned rapid prototyping flame-retardant nylon composite material, which is characterized by comprising the following steps:

[0030] The MXD6 resin, decabromodiphenylethane flame retardant, antimony trioxide and polyethylene glycol are uniformly mixed and melt-extruded to obtain a rapid molding flame-retardant nylon composite material.

[0031] Specifically, the above-mentioned melt extrusion adopts a twin-screw extruder; the temperature of the screw zones 1 to 10 of the twin-screw extruder is set as follows: the temperature of zone 1 is 70°C to 90°C, the temperature of zone 2 is 170°C to 190°C, the temperature of zone 3 to zone 4 is 260°C to 280°C, the temperature of zone 5 to zone 9 is 240°C to 260°C, and the temperature of zone 10 is 250°C to 270°C; the screw speed of the twin-screw extruder is 300 to 500rpm.

[0032] The use of the above rapid prototyping flame-retardant nylon composite material in the preparation of electronic and electrical component materials is also within the protection scope of the present invention.

[0033] The present invention also protects an electronic and electrical component comprising the rapid prototyping flame-retardant nylon composite material.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The rapid prototyping flame-retardant nylon composite material of the present invention selects a specific type of nylon resin, combines a decabromodiphenylethane flame retardant and polyethylene glycol with a specific number average molecular weight, and utilizes the high glass transition temperature of the MXD6 resin to provide a basis for high-beat rapid prototyping; at the same time, the low melting point is adapted to the decabromodiphenylethane flame retardant with a low specific heat capacity, and the polyethylene glycol with a specific number average molecular weight can quickly migrate to the polymer surface to form a melt film to assist the demolding of the flame-retardant nylon composite material, thereby making the nylon composite material have a flame retardant grade of V-0 and excellent rapid prototyping ability. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0037] 1. Raw materials and reagents

[0038] MXD6 resin 1, melting point is 237°C, relative viscosity measured according to ISO 307-2007 standard is 2.0, brand is PA6 MXD6 M20L, manufacturer is Beijing Anage Energy Engineering Technology Co., Ltd.;

[0039] MXD6 resin 2, melting point is 238°C, relative viscosity measured according to ISO 307-2007 standard is 2.5, brand is PA6 MXD6 M25L, manufacturer is Beijing Anage Energy Engineering Technology Co., Ltd.;

[0040] MXD6 resin 3, melting point is 237°C, relative viscosity measured according to ISO 307-2007 standard is 3.0, brand is PA6 MXD6 M30L, manufacturer is Beijing Anage Energy Engineering Technology Co., Ltd.;

[0041] PA66 resin, melting point is 263℃, brand is PA66 EPR24, manufacturer is Pingdingshan Shenma Group;

[0042] PA6 resin, melting point is 221℃, brand name is PA6 HY2800, manufacturer is Jiangsu Haiyang Chemical Fiber Co., Ltd.;

[0043] Decabromodiphenylethane flame retardant, brand name SAYTEX 8010, manufacturer is American Albemarle Group;

[0044] Polystyrene flame retardant, brand name SAYTEX HP-5010PST, manufacturer is American Albemarle Group;

[0045] Brominated epoxy flame retardant, brand F-2100, manufacturer is Israel Chemical Group;

[0046] The synergistic flame retardant antimony trioxide was commercially available and the same type was used in all parallel experiments;

[0047] PEG-800, number average molecular weight is 800, the manufacturer is Lotte Chemical of South Korea;

[0048] PEG-1000, number average molecular weight is 1000, manufacturer is Lotte Chemical of South Korea;

[0049] PEG-1500, number average molecular weight is 1500, manufacturer is Lotte Chemical of South Korea;

[0050] PEG-4000, number average molecular weight is 4000, the manufacturer is Lotte Chemical of South Korea;

[0051] PEG-6000, number average molecular weight is 6200, manufacturer is Lotte Chemical of South Korea;

[0052] PEG-8000, number average molecular weight is 8200, the manufacturer is Lotte Chemical of South Korea.

[0053] 2. The rapid prototyping flame-retardant nylon composite materials of the embodiments and comparative examples of the present invention are prepared by the following preparation method:

[0054] After weighing each component according to the formula and mixing them evenly, the components are added into a twin-screw extruder for melt blending and extrusion granulation to obtain a rapid molding flame-retardant nylon composite material;

[0055] Among them, the melt extrusion conditions of the twin-screw extruder are: the temperature of zone 1 is 80°C, the temperature of zone 2 is 180°C, the temperature of zone 3 is 270°C, the temperature of zone 4 is 270°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 250°C, the temperature of zone 7 is 250°C, the temperature of zone 8 is 250°C, the temperature of zone 9 is 250°C, the temperature of zone 10 is 260°C, and the main engine speed is 300-500r / min.

[0056] 3. Performance testing

[0057] (1) Characterization of rapid prototyping of composite materials

[0058] ① The injection molding limit cooling time T is based on the smooth demolding of the injection molding standard sample without the top convex deformation phenomenon. The shortest cooling time is obtained in seconds. The size of the standard sample is: 60mm*60mm*2.0mm;

[0059] ② Under the same cooling time conditions, when the mold opening action is completed, the surface temperature of the plastic part is C, in degrees Celsius, obtained by the temperature sensor;

[0060] ③Specific heat capacity Cp, according to ISO 11357-4-2021, Plastics--Differential scanning calorimetry (DSC)--Part 4: Determination of specific heat capacity, select a fixed temperature point of 120°C, the unit is J / gK.

[0061] (2) The flame retardant grade test refers to UL 94 standard, and the test specimen size is 125mm*13mm*0.5mm.

[0062] Examples 1 to 10

[0063] The weight proportions of the components of the rapid prototyping flame-retardant nylon composite materials in Examples 1 to 10 are shown in Tables 1 and 2.

[0064] Table 1 Rapid prototyping flame retardant nylon composite materials in Examples 1 to 6

[0065]

[0066] Table 2 Rapid prototyping flame retardant nylon composite materials in Examples 7 to 10

[0067]

[0068] Comparative Examples 1 to 6

[0069] The weight proportions of the components in the rapid prototyping flame-retardant nylon composite materials in Comparative Examples 1 to 6 are shown in Table 3.

[0070] Table 3 Rapid prototyping flame retardant nylon composite materials in comparative examples 1 to 6

[0071]

[0072]

[0073] The performance test results of the rapid prototyping flame-retardant nylon composite materials in various embodiments and comparative examples according to the above-mentioned method are shown in Table 4.

[0074] Table 4 Test results of various embodiments and comparative examples

[0075]

[0076] It can be seen from the data in Table 4 that the flame retardant grade of the rapid prototyping flame-retardant nylon composite material of the present invention can achieve UL94 V-0 flame retardancy and has good flame retardant performance; the ultimate cooling time T of the rapid prototyping flame-retardant nylon composite material is 1 to 5s, and the surface temperature of the workpiece is only 84 to 93°C, which shows that the nylon composite material has excellent rapid prototyping ability.

[0077] It can be seen from Examples 1 to 3 that the cooling time of the workpiece increases slightly with the increase of the relative viscosity of the MXD6 resin, while the mold surface temperature and specific heat capacity show an increasing trend. This is mainly due to the increase in the viscosity of the MXD6 resin, which leads to an increase in the shear heat of the nylon composite material during the injection molding process, thereby increasing the melt temperature and reducing the cooling efficiency.

[0078] Comparative Examples 1 and 2 use conventional PA66 resin and PA6 resin, respectively. The cooling time required for molding is significantly increased, reaching 8s and 11s, respectively. At the same time, the surface temperature of the parts also reaches 104°C and 109°C, indicating that when PA66 resin or PA6 resin is used as the resin matrix, the molding limit cooling time and the surface temperature of the parts will be increased.

[0079] Comparative Examples 3 and 4 respectively use low number average molecular weight PEG-800 and high number average molecular weight PEG-8000, and their corresponding cooling time is significantly increased, and the surface temperature of the workpiece is also above 100°C, which fully demonstrates that when the molecular weight of polyethylene glycol is too high or too low, it cannot meet the requirements of rapid prototyping.

[0080] Comparative Examples 5 and 6 use brominated polystyrene and brominated epoxy flame retardants as flame retardants, respectively. Compared with the decabromodiphenylethane flame retardant, their cooling time and specific heat capacity are significantly increased, making it difficult to effectively improve the rapid molding performance of nylon composite materials.

[0081] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A rapid prototyping flame-retardant nylon composite material, characterized in that: By weight, it includes the following components: MXD6 resin 70-90 parts; 18-24 parts of decabromodiphenylethane; 1-5 parts of polyethylene glycol; 6-10 parts of antimony trioxide; Wherein, the number average molecular weight of the polyethylene glycol is 1000~6200.

2. The rapid prototyping flame-retardant nylon composite material according to claim 1, characterized in that: By weight, it includes the following components: MXD6 resin 75-85 parts; Decabromodiphenylethane 20-22 parts; 1~3 parts of polyethylene glycol 6-10 parts of antimony trioxide.

3. The rapid prototyping flame-retardant nylon composite material according to claim 1, characterized in that: The number average molecular weight of the polyethylene glycol is 1500-4000.

4. The rapid prototyping flame-retardant nylon composite material according to claim 1 or 3, characterized in that: The mass percentage of the polyethylene glycol relative to the rapid prototyping flame-retardant nylon composite material is 0.84% ​​to 4.85%.

5. The rapid prototyping flame-retardant nylon composite material according to any one of claims 1 to 3, characterized in that: The relative viscosity of the MXD6 resin measured according to ISO 307-2007 standard is 2.0-3.

0.

6. A method for preparing the rapid prototyping flame-retardant nylon composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The rapid molding flame retardant nylon composite material is obtained by mixing MXD6 resin, decabromodiphenylethane, antimony trioxide and polyethylene glycol and melt-extruding the mixture.

7. The method for preparing a rapid prototyping flame-retardant nylon composite material as claimed in claim 6, characterized in that: The temperature of the melt extrusion is 240-280° C.; the equipment of the melt extrusion is a twin-screw extruder, and the screw speed is 300-500 rpm.

8. Use of the rapid prototyping flame-retardant nylon composite material according to any one of claims 1 to 5 in the preparation of electronic and electrical component materials.

9. An electronic and electrical component, characterized in that: The electronic and electrical component comprises the rapid prototyping flame-retardant nylon composite material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • V2-grade flame-retardant nylon material and preparation method thereof

    CN102746646A

  • Flame-retardant antistatic nylon material and preparation method thereof

    CN110256843A